Problemy oceny opłacalności podatkowej spółki osobowej i kapitałowej - Poszwa, Michał (The Problems of Tax Profitability Evaluation in Personal Partnerships and Capital Companies, 2006)
In Polish law there are different rules of taxing incomes of personal partnerships and capital companies. Different lax treatment of personal partnerships and capital companies is very controversial. There is a problem appearing, whether the different charging of both kinds of companies interferes with the wide range of competition rules. Moreover, the different (axing of personal partnerships and capital companies causes the necessity of deciding which form is more profitable for the taxpayer. Setting the cost-effectiveness is very difficult and demands using profit calculation. The final decision about form of business activity is very risky.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1139, s. 340-352